2022
DOI: 10.1111/epi.17378
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy of the hippocampal CA1 subfield relates to long‐term forgetting in focal epilepsy

Abstract: Objective:The mechanisms underlying accelerated long-term forgetting (ALF) in patients with epilepsy are still under investigation. We examined the contribution of hippocampal subfields and their morphology to long-term memory performance in patients with focal epilepsy. Methods:We prospectively assessed long-term memory and performed magnetic resonance imaging in 80 patients with focal epilepsy (61 with temporal lobe epilepsy and 19 with extratemporal lobe epilepsy) and 30 healthy controls. The patients also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Although autobiographical episodic memory has not been tested by the VLMT in this study population, these results indicate the role of CA3 in episodic memory consolidation ( 37 , 38 ). Finally, controversial findings have also been shown regarding the role of CA1 in verbal memory performance; some studies have reported correlations between CA1 neural density ( 39 ) and volumes ( 28 , 36 ) with immediate and delayed verbal memory recall as well as long-term memory consolidation ( 8 ), while other studies have shown opposite findings ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although autobiographical episodic memory has not been tested by the VLMT in this study population, these results indicate the role of CA3 in episodic memory consolidation ( 37 , 38 ). Finally, controversial findings have also been shown regarding the role of CA1 in verbal memory performance; some studies have reported correlations between CA1 neural density ( 39 ) and volumes ( 28 , 36 ) with immediate and delayed verbal memory recall as well as long-term memory consolidation ( 8 ), while other studies have shown opposite findings ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…For figural memory, the percentile ranks of the DCS served as outcome measure and all subfield volumes of the right hippocampi were entered into the regression analysis as predictors. The following subfields were entered into regression analyses: subiculum, presubiculum, and parasubiculum added to subicular complex (SUB) ( 8 , 26 ), cornu ammonis 1 (CA1), cornu ammonis 2/3 (CA2/CA3), cornu ammonis 4 (CA4), granule cells in the molecular layer of the dentate gyrus (GC-ML-DG), molecular layer, hippocampal amygdala transition area (HATA), fimbria, hippocampal tail and hippocampal fissure. One-way analysis of variance (ANOVA) was used to compare the age among groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Volumetric changes, quantified through 3-T structural neuroimaging, have been demonstrated between controls and patients with epilepsy across these subfields. 8,9 More recently, ultra-high-field 7-T scanners with hippocampus-specific imaging protocols have been used to provide greater contrast in these subfields, allowing for the interrogation of more subtle volumetric, [10][11][12][13] functional, 14 and even neurotransmitter expression 15 changes.…”
Section: Introductionmentioning
confidence: 99%
“…As this is useful diagnostic information, automated segmentation algorithms have been developed and successfully used to segment hippocampal subfields from magnetic resonance images 5–7 . Volumetric changes, quantified through 3‐T structural neuroimaging, have been demonstrated between controls and patients with epilepsy across these subfields 8,9 . More recently, ultra‐high‐field 7‐T scanners with hippocampus‐specific imaging protocols have been used to provide greater contrast in these subfields, allowing for the interrogation of more subtle volumetric, 10–13 functional, 14 and even neurotransmitter expression 15 changes.…”
Section: Introductionmentioning
confidence: 99%